Assistance technology in health promotion: care and selfcare of insulin dependent elderly - Arethusa Morais de Gouveia Soares; Gerídice Lorna Andrade de Moraes; Rui de Gouveia Soares Neto; Marilia Braga Marques; Maria Josefina da Silva (Rev Rene)
This article aimed to report the experience lived by the nursing professionals in a group of insulin-dependent elderly patients with the assistance technology practice. Twelve patients participated in the group, eight caregivers, a doctor, a nurse a one medical student. The encounter presented four different moments. In the first moment the user participated only as an observer, learning how to manipulate correctly the material, how to apply the medication and how to storage the bottles. In the second moment the user became agent of transformation of his own care. In the third moment the difficulties and doubts were exposed and in the fourth moment the encounter was evaluated. Those professionals’ attitude of summoning the insulin patients for a collective orientation resulted, after the encounter evaluation, in the creation of a new support group, so that several themes concerning the daily life of "having diabetes and using insulin" could be approached.